Let $Sp(2n):=\{A\in\mathbb{R}^{2n\times 2n}\mid A^tA_0A=A_0\}$ be the group of symplectomorphisms from $(\mathbb{R}^{2n},\omega_0)$ to itself, where:

\begin{gather} A_0 := \begin{bmatrix}{} 0 & I\\ -I & 0\\ \end{bmatrix}\in\mathbb{R}^{2n\times 2n} \end{gather}

represents the standard symplectic form $\omega_0$ with respect to the canonical basis of $\mathbb{R}^{2n}$. Prove that $Sp(2n)$ is an embedded submanifold of $GL(2n)$ and has dimension $2n^2+n$.

I know the essential idea is to look at the map: \begin{align*} f:GL(2n)&\to \text{Sympl}(2n)\\ A & \mapsto A^tA_0A \end{align*}

where $\text{Sympl}(2n):=\{A\in\mathbb{R}^{2n\times 2n}\mid A=-A^t\text{ and }\det A\neq 0\}$, which is the submanifold of symplectic forms and has dimension $\frac{(2n)^2-2n}{2}$.

Considering that $f$ is a submersion, we have $Sp(2n)=f^{-1}(A_0)$ is an embedded submanifold with dimension $\dim (GL(n))-\dim (\text{Sympl}(2n))=(2n)^2-\left(\frac{(2n)^2-2n}{2}\right)=2n^2+n$ by the Regular Value Theorem.

My question is really basic: how do I prove $f$ is a submersion? I've tried to calculate $df_A(M)$ by taking the curve $\alpha(t)=A+tM$, so that: \begin{align*} df_A(M)&=(f\circ \alpha)'(0)\\ &=(A^tA_0A+tA^tA_0M+tM^tA_0A+t^2M^tA_0M)'(0)\\ &=A^tA_0M+M^tA_0A \end{align*} but I don't know how to prove this is surjective, and it seems complicated. Is there some trick to it? Or is there a better way?


First I have to say that my answer is really similar to the one already cited in the comments, I just want to focus a little more one the surjectivity part that was explicitly asked for in your question. So, we would like to prove that $$df_A\colon M\mapsto A^tA_0M+M^tA_0A$$ is surjective onto the space of skew-symmetric $2n\times 2n$ matrices. In order to use the regular value theorem, it is enough to do so for any $A$ such that $f(A)=A_0$, i.e. $A^tA_0A=A_0$. For any such $A$, we have $f(A)=f(I)$, where $I$ is the unit matrix. For any $A'\in\mathrm{GL}(2n)$, let $\varphi_{A'}\colon \mathrm{GL}(2n)\rightarrow \mathrm{GL}(2n)$ denote multiplication with $A'$. Then $$f(A)=f(I)=f\circ \varphi_{A^{-1}}(A),$$ i.e. $$df_A=df_I\circ d(\varphi_{A^{-1}})_A.$$ As $d(\varphi_{A^{-1}})_A$ clearly is bijective, we only need to prove $df_I$ surjective. (this is still all as in the answer cited above/in the comments.) From here, let us do the explicit calculations: $d(\varphi_{A^{-1}})_A\colon T_A\mathrm{GL}(2n)\rightarrow T_I\mathrm{GL}(2n)$ is given by $M\mapsto A^{-1}M$, so we would like to solve $$df_I(M')=A_0M'+M^tA_0'=A_0M'-(A_0M')^t=B$$ for a given (skew-symmetric) $B$, where $M'=A^{-1}M$ with $M$ satisfying $df_A(M)=B$. We might simplify this by setting $M'':=A_0M'$, to get $$M''-(M'')^t=B.$$ Here, maybe a little trick is involved, as one needs to recall that $B$ was taken from skew-symmetric matrices, so $B^t=-B$, in particular, $B-B^t=2B$, which gives the solution $M''=\frac{1}{2}B$, i.e. $$M=AM'=-AA_0M''=-\frac{1}{2}AA_0B$$ has the desired property $df_A(M)=B$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.